2015
DOI: 10.3390/w7020634
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Streamflow Trends in Northern Taiwan

Abstract: Abstract:Streamflow is an important factor in the study of water resource management, floods, and droughts. Dramatic climate change has created extreme rainfall distributions, making the study of streamflow trends and variability even more crucial. In this study, the long-term streamflow data and trends recorded at gauging stations in Northern Taiwan are analyzed using the Mann-Kendall test. The data used for trend analysis are the average annual streamflow, the average seasonal streamflow, and the high and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 26 publications
(28 reference statements)
0
33
1
Order By: Relevance
“…The hydroclimatic variables analyzed generally include precipitation amount, surface air temperature, evapotranspiration, and streamflow [8][9][10][11][12]. The previous precipitation studies have focused mainly on changes in annual or monthly precipitation amounts and have ignored changes in precipitation structure including precipitation amount, mean precipitation intensity, and precipitation frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydroclimatic variables analyzed generally include precipitation amount, surface air temperature, evapotranspiration, and streamflow [8][9][10][11][12]. The previous precipitation studies have focused mainly on changes in annual or monthly precipitation amounts and have ignored changes in precipitation structure including precipitation amount, mean precipitation intensity, and precipitation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some studies related to trend analysis of hydroclimatic variables at watershed scale have been carried out, for example in the Lake Victoria Basin in East Africa [5], the Yellow River Basin [6], and the Three Gorges Reservoir [7]. The hydroclimatic variables analyzed generally include precipitation amount, surface air temperature, evapotranspiration, and streamflow [8][9][10][11][12]. The previous precipitation studies have focused mainly on changes in annual or monthly precipitation amounts and have ignored changes in precipitation structure including precipitation amount, mean precipitation intensity, and precipitation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the distributions of streamflow and precipitation have similar trends in each month; in months with greater precipitation, there is also an increase in streamflow volume. Yeh et al [33] used the Mann-Kendall test to analyze the streamflow data recorded over 30 years from 12 gauge stations in the northern region, which are not affected by artificial water conservancy facilities, in order to explore the streamflow trend characteristics in the northern region. Table 2 and Figure 2 respectively show the details and spatial distribution of these stations.…”
Section: Study Areamentioning
confidence: 99%
“…Therefore, in order to lower the impact of climate change on water usage, effective study and management of the hydrological information in the northern region is necessary. Yeh et al [33] used the Mann-Kendall test, Theil-Sen estimator, Mann-Whitney-Pettit test and the cumulative deviation test to investigate the streamflow trend characteristics in northern Taiwan. The Mann-Kendall test was used to analyze the streamflow trend [34][35][36][37][38][39], and the Theil-Sen estimator was used to calculate the trend slopes to obtain the extent of trend changes [40][41][42][43][44].The Mann-Whitney-Pettit test and the cumulative deviation test, two tests commonly used in hydrology analyses, are used to find the change points [43,[45][46][47].…”
mentioning
confidence: 99%
See 1 more Smart Citation